2013
DOI: 10.1017/s1461145712001137
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PDYN gene with alcohol dependence and the propensity to drink in negative emotional states

Abstract: Synthetic kappa-opioid receptor (KOR) agonists induce dysphoric and pro-depressive effects, and variations in the KOR (OPRK1) and prodynorphin (PDYN) genes have been shown to be associated with alcohol dependence. We genotyped 23 single nucleotide polymorphisms (SNPs) in the PDYN and OPRK1 genes in 816 alcohol dependent subjects and investigated their association with (1) negative craving measured by a subscale of the Inventory of Drug Taking Situations (IDTS); (2), a self-reported history of depression; and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 50 publications
4
52
1
Order By: Relevance
“…While much of the published data have been obtained from experimental animal studies (15,16,35), recent clinical investigations have also demonstrated that variants of the PDYN gene relate to transcriptional alterations of PDYN mRNA expression and are associated with depressive traits and negative craving in alcoholics (36,37). The current study adds to the field by directly examining the human brain to provide neuropathophysiological insights that have not been previously reported.…”
Section: Figurementioning
confidence: 85%
“…While much of the published data have been obtained from experimental animal studies (15,16,35), recent clinical investigations have also demonstrated that variants of the PDYN gene relate to transcriptional alterations of PDYN mRNA expression and are associated with depressive traits and negative craving in alcoholics (36,37). The current study adds to the field by directly examining the human brain to provide neuropathophysiological insights that have not been previously reported.…”
Section: Figurementioning
confidence: 85%
“…A recent paper reported an association of the PDYN gene with alcohol dependence and the propensity to drink in negative emotional states. Further an association of a PDYN variant with drinking to avoid emotional or somatic discomfort was also reported (Karpyak et al, 2013; Preuss et al, 2013). …”
Section: Genetic Mapping Studies Of Aud: Linkage and Candidate Gene Amentioning
confidence: 92%
“…Recent studies of humans of European-American descent demonstrate that variations in the genes encoding KOR and dynorphin, OPRK1 and PDYN, are associated with alcohol dependence (Xuei et al, 2006;Edenberg et al, 2008;Karpyak et al, 2012). In addition, animal studies using rats show that activation of KORs with a selective KOR agonist reduces voluntary ethanol intake (Lindholm et al, 2001), whereas a selective KOR antagonist increases alcohol self-administration (Mitchell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%